ELT and Entrepreneurship: Motivating Learners to Create Their Own Opportunities - Khatri , Man Bahadur; Khatri , Niru Panday (Educational Journal, 2025)
This article began as a conversation and experience-sharing session with students. It aims to motivate students toward entrepreneurship and leadership in the 21st century. English is commonly used in business, education, diplomatic communication, and bilateral exchanges between organizations such as universities and public affairs. At the same time, it functions as a 'global lingua franca' for people traveling all over the world. In non-native countries like Nepal, English enjoys its superiority through scholarships, high prestige, and good incomes. In recent days, when ELT learners in universities in Nepal feel as if they do not get better jobs after receiving their degree certificates, this article can support them in finding their own path. Instead of hunting for jobs in the market, this article motivates young ELT learners to create their own business using the English language and ELT skills. Using an experiential and self-expressive style as a methodology, this article suggests that ELT learners have passion, a dream, and dedication in their learning and performance. The more they create zeal within themselves, the better opportunities they can get in the markets because of the English language and ELT skills.